A review of the use of prebiotic in aquaculture for fish and shrimp - Mehdi Yousefian; Mojtaba Sheikholeslami Amiri (Advances in Aquaculture and Fisheries Management, 2020)
It has been documented in a number of food animals that gastrointestinal bacteria play important roles in affecting the nutrition and health of the host organism. Thus, various means of altering the intestinal bacteria to achieve favorable effects such as better resistance to pathogens, enhancing growth and immune stimulation of the host organism have been investigated in various fish and shrimp. In this respect, probiotics and prebiotics are used in farm animal and for aquaculture, although the probiotic approach has been extensively used and advocated, viability after ingestion is difficult to guarantee and almost impossible to prove. The prebiotic concept dictates that non viable dietary components fortify certain components of the intestinal flora. This concept has the advantage that survival of the ingested ingredient through the upper gastrointestinal tract is not a prerequisite because it is indigenous bacterial genera that are targeted. Despite some positive effects prebiotic supplements on fish and crustaceans have been published however it seems such information for aquatic organism is inadequate. This paper will give short review of recent studies in which the effects of various prebiotics have been evaluated for potential application in the aquacultural production of fish and shrimp.